Correlates of cigarette smoking among male college students in Karachi, Pakistan - Akhtar Saeed; Butt Zahid A; Rozi Shafquat (BMC, 2007)
Abstract Background About 1.3 billion people are regular smokers world wide and every day between 8,200 and 9,900 young people start to smoke, risking rapid addiction to nicotine. Transition from high school to college is a critical period to adopt healthy habits and life style. Therefore, it is important to understand the factors that might influence their smoking habit. Our study aims to assess the influence of factors that encourage college students to smoke cigarettes. Methods The data used in this survey were obtained from a representative sample of registered colleges of Karachi. A random sample of 576 male college students of ages ranging from 15-30 years was interviewed using a questionnaire administered by survey officers, by applying multi stage cluster sampling during the academic year 2004-2005. Results In this study, we found 26.7% of students had ever tried smoking, whereas 24%(95% CI: 21.0%-28.0%) of college students reported current smoking (that is whether one had smoked a cigarette in past 30 days). Among different age groups, prevalence of current smoking was 19.2% in 15-17 years, 26.5% in 18-20 years and 65% in 21 years and above. After adjusting for age of respondent, students in public schools were more likely to smoke as compared to students in private schools (adjusted OR = 2.3; 95% CI: 1.3-4.2). Students whose friends are smokers were 5 times more likely to smoke compared to those whose friends are non-smokers (adjusted OR = 4.8; 95%CI: 3.1 - 7.4). Those students having fathers with no formal schooling were more likely to smoke (adjusted OR = 2.2; 95% CI: 1.1-4.2) as compared to those whose fathers had some degree of education. Students having non-working mothers were more likely to smoke as compared to students with working mothers (adjusted OR = 2.8; 95% CI: 0.9-9.1). Students belonging to Bin Qasim (adjusted OR = 2.1; 95% C.I: 1.1-4.1) and Gadap town (adjusted OR = 2.1; 95%C.I) were more likely to smoke as compared to students residing in other towns. Conclusion This study shows that smoking is strongly associated with age, which may suggest social tolerance to smoking in this setting and that social and educational variables appear to play a significant role in smoking among college students. Our study suggests that such factors should be taken into account when designing effective tobacco control programs among college students. This is an effort which has been done to reduce tobacco consumption among college students and introduce awareness programs to amend their health risk behavior.